2012
DOI: 10.1596/26828
|View full text |Cite
|
Sign up to set email alerts
|

Micro-Determinants of Informal Employment in the Middle East and North Africa Region

Abstract: This note assesses the main micro-determinants of informal employment in the Middle East and North Africa (MENA) region from a human development stand point. It's main purpose is to quantify the patterns of labor informality (defined as the share of all employment with no access to social security) according to age, gender, education level, employment sector, profession, marital status, employment status, and geographic area in a selected group of countries in the region. Results indicate that the size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 4 publications
1
20
0
Order By: Relevance
“…We carry the analysis distinguishing between these different types of workers because, as discussed earlier, the SI laws and regulations vary by workers' wage/sector status, which in turn may have important implications on the likelihood of access to SI among each type of worker. We control for the set of covariates commonly used in the informality and access to SI literature and available in our datasets (Auerbach et al, 2007;Pagés & Madrigal, 2008;Angel-Urdinola & Tanabe, 2012). The worker-specific characteristics vector, X i , consists of a dummy for being a woman, a dummy for being ever married (never married being the reference category), age and its square, the education level [categorically as illiterate and read and write (the reference), less than secondary, secondary and above secondary], years of experience and its square, and the occupation level [categorically as white collar high skilled (the reference), white collar low skilled, blue collar high skilled and blue collar low skilled].…”
Section: Determinants Of Access To Social Insurancementioning
confidence: 99%
See 1 more Smart Citation
“…We carry the analysis distinguishing between these different types of workers because, as discussed earlier, the SI laws and regulations vary by workers' wage/sector status, which in turn may have important implications on the likelihood of access to SI among each type of worker. We control for the set of covariates commonly used in the informality and access to SI literature and available in our datasets (Auerbach et al, 2007;Pagés & Madrigal, 2008;Angel-Urdinola & Tanabe, 2012). The worker-specific characteristics vector, X i , consists of a dummy for being a woman, a dummy for being ever married (never married being the reference category), age and its square, the education level [categorically as illiterate and read and write (the reference), less than secondary, secondary and above secondary], years of experience and its square, and the occupation level [categorically as white collar high skilled (the reference), white collar low skilled, blue collar high skilled and blue collar low skilled].…”
Section: Determinants Of Access To Social Insurancementioning
confidence: 99%
“…This high cost of SI causes many employers to negotiate higher pay, with their potential employees, in return of not having SI coverage or to report lower basic wage and then the actual salary of their worker to the SI authority (Sieverding & Selwaness, 2012;Roushdy & Selwaness, 2015). These factors resulted in the expansion of informal wage work, which lacks any type of social protection benefits, in Egypt as in similar developing countries (Perry et al, 2007;Angel-Urdinola & Tanabe, 2012;Gatti, Bodor, Angel-Urdinola, & Silva, 2014). Furthermore, the SI coverage gap among non-wage workers has been even larger.…”
Section: Introductionmentioning
confidence: 99%
“…The wider environment for innovation has been unpropitious. The informal economy has remained very large – a recent estimate suggested that over two‐thirds of the labour force is in informality (Angel‐Urdinola and Tanabe, ) – but has operated at generally low levels of productivity and with poor incentives to make the transition to the formal economy. Consequently, productivity levels in the Arab world have on average remained relatively low…”
Section: Sources and Dimensions Of Underperformance: Diagnosticsmentioning
confidence: 99%
“…They perceive informality from the point of view of firms, workers and untaxed activities [19]. They assert that informality constitute of small unregistered firms, with employers and employees as well as the self-employed individuals working on their own or in family businesses.…”
Section: Informality: From Theory To Practicementioning
confidence: 99%
“…They assert that informality constitute of small unregistered firms, with employers and employees as well as the self-employed individuals working on their own or in family businesses. With respect to taxation, they argue that informality consists of activities that are hidden from taxation [19].…”
Section: Informality: From Theory To Practicementioning
confidence: 99%